Nurturing accountability practices among bureaucrats : what contextual factors tell us? - Nurul Liyana Mohd Kamil,; Sherilyn Emariza Shariffuddin,; Nur Hairani Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study was carried out to scrutinise the influence of internal factors (in the form of the integrity system, internal control system, and leadership qualities) on the accountability practices among bureaucrats. A total of 371 bureaucrats participated in the study, representing an 86.3 per cent response rate. Findings from multiple linear regression demonstrated that integrity system and leadership qualities were significantly related to accountability practices. The influence of internal control systems, however, is not supported. Research on the determination of accountability practices among bureaucrats, particularly in the Malaysian public sector, is vital but remains scarce. The findings can serve as empirical points by offering some insight on accountability practices among bureaucrats, thus benefitting policymakers in executing human capital policies and nurturing better service performance to the nation.